Clinicopathological Characteristics and Influencing Factors of Renal Vascular Lesions in Anti-neutrophil Cytoplasmic Autoantibody-Related Renal Vasculitis - Wang, Ruiqiang; Wu, Yunqi; Zhang, Xiaofeng; An, Dongyue; Guo, Ningning; Guo, Yuanyuan; Wang, Jin; Tang, Lin (Frontiers in Medicine, 2021)
The purpose of this study was to evaluate the clinicopathological features of different degrees of extraglomerular renal vascular lesions (RVLs) in patients with ANCA-associated renal vasculitis and to explore their clinical determinants. This study is a retrospective study of 186 patients with ANCA-associated renal vasculitis diagnosed in the First Affiliated Hospital of Zhengzhou University from January 2014 to April 2019. The patients who met the inclusion criteria were divided into non-renal RVLs, mild RVLs, moderate RVLs and severe RVLs. It was found that there were significant differences in SCR, eGFR, ESR, HDL, SBP, the prevalence rate of hypertension, the proportion of normal glomeruli, the proportion of sclerotic glomeruli and interstitial fibrosis integral. SCR and ESR are independent risk factors for RVLs. Participants were followed up for 1-year, and progression to end stage renal disease and death were defined as endpoint events. We found that the survival rate of patients without RVLs was significantly higher than that of patients with RVLs, and the RVLs was an independent risk factor for end state renal diseas (ESRD) or death. Early intervention of the progression of RVLs can improve the prognosis.